Comparative theoretical analysis between types of structural reinforcement applied in reinforced concrete beam (Research, Society and Development, 2021)
There are several structures that are going through a load increase process, either by adding rooms or changing the use of the current environment. For this to occur without compromising the physical integrity of its users and the structure, it is necessary to use structural reinforcements, which serve to increase the performance of the structure, equipping it with more rigidity/or resistance. The research aimed to describe the main advantages and disadvantages of reinforcement techniques in reinforced concrete beams by external prestressing, bonding and/or anchoring steel sheets, bonding carbon fibers and the jacketing method. So that you can make the decision on which technique to use. The methodology of this work is based on a descriptive bibliographic research. Using the comparative method, which studies the differences and similarities between different facts. The choice of the most appropriate reinforcement technique must be made after a careful evaluation of the main characteristics of the piece to be reinforced and the methods that can be used. The definition can be based on: reinforcement performance, preservation of the architecture, application cost and ease and speed of installation and ease of finding the material for labor.